Effect of Oil Palm Frond-Derived Carboxymethyl Cellulose (CMC) on the Physicochemical and Sensory Characteristics of Chili Sauce - Muhammad Arif; Sri Wahyuna Saragih; Ritna Wahyuni (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Oil palm fronds are abundant agricultural biomass with high cellulose content that can be converted into carboxymethyl cellulose (CMC) as a natural food thickener. This study aimed to evaluate the effect of oil palm frond-derived CMC on the physicochemical and sensory characteristics of chili sauce and to determine the optimum CMC concentration. A completely randomized design was applied using four CMC concentrations (0, 0.5, 1.0, and 1.5%) with three replications for each treatment. The evaluated parameters included moisture content, pH, crude fiber, texture, vitamin C, viscosity, aroma, and taste. Data were analyzed using one-way analysis of variance followed by Duncan's multiple range test at a 5% significance level. The results showed that increasing CMC concentration significantly reduced moisture content from 84.55% to 83.30% while increasing pH from 3.97 to 4.15, crude fiber from 1.24% to 1.72%, texture from 1.33 to 2.14 N, vitamin C from 22.81 to 24.44 mg/100 g, and viscosity from 2,334.33 to 4,275.00 cP (p < 0.05). Sensory evaluation also showed significant differences, with the 1.0% CMC treatment receiving the highest aroma (4.80) and taste (4.90) scores. These findings indicate that oil palm frond-derived CMC can serve as an effective natural thickening agent for chili sauce, with a concentration of 1.0% providing the best balance between physicochemical quality and consumer acceptance.